Peran Kecerdasan Buatan Dalam Pengambilan Keputusan Pengelolaan Lingkungan di Wilayah Tropis - Efendi Hamka; Rufaidah Rufaidah; Nirmala Sari (Trends Research of Environmental Studies, 2025)
Tropical regions exhibit complex, dynamic environmental characteristics and are highly vulnerable to pressures arising from climate change and human activities. These conditions necessitate environmental management approaches that are adaptive, data-driven, and capable of supporting accurate and timely decision-making. This study aims to examine the role of artificial intelligence in environmental management decision-making in tropical regions. The research employs a qualitative approach through a systematic literature review of open-access scientific journal articles published over the past ten years and relevant to the topics of artificial intelligence and environmental management. The data were analyzed using thematic analysis techniques to identify patterns, trends, and the major contributions of artificial intelligence to environmental management. The findings indicate that artificial intelligence plays a significant role in enhancing the effectiveness of environmental monitoring, strengthening predictive and modeling capabilities of environmental systems, and supporting evidence-based decision support systems. The application of artificial intelligence has proven relevant in the management of water resources, air quality, biodiversity, renewable energy, and climate change mitigation in tropical regions. However, the effectiveness of implementing this technology is strongly influenced by data quality, infrastructure readiness, institutional capacity, and supportive policy frameworks. This study concludes that artificial intelligence has substantial potential as a decision-support tool for environmental management in tropical regions, provided that it is implemented in a contextual, ethical, and long-term sustainability-oriented manner.